‘Right Paths’ and/or ‘Paths of Righteousness’?: Examining Psalm 23.3b within the Psalter - Abernethy, Andrew T. (Journal for the study of the Old Testament, 2015)
There are various interpretations of ‭קדע־ילגעמב‬ ‭ינחני‬ in Ps. 23.3b. Does it profess confidence in Yahweh's guidance of his people to live morally, his righteous treatment of them, his ensuring their prosperity, or some combination of these? This article contributes to the discussion by drawing upon the literary context of the Psalter for assistance in several ways. First, with the Psalter providing a ‘grammar of faith’ for its readers, seven verses containing collocations similar to Ps. 23.3b receive consideration to discern what sense they typically convey (Pss. 1.6; 5.9; 25.9; 27.11; 107.7; 119.35; 139.24). Second, this article explores how the frame of Book I and Psalms 15–24, a smaller collection within Book I, illuminate how one might read Ps. 23.3 within these contexts. Thus, the Psalter as a collocative and structural context is brought to bear on the interpretation of Ps. 23.3b.